RADIATION DOSE AND ANATOMICAL INFORMATION IN SACRUM BONE EXAMINATION WITH AP AND AXIAL AP PROJECTIONS - Rini Indrati; Siti Daryati; Dewi Kartikasari; Sri Mulyati; Marichatul Jannah (Jurnal Riset Kesehatan, 2021)
The projections for the sacrum are axial anteroposterior with the beam 15 degrees toward the cephalad, and axial posteroanterior in the direction of the beam 15 degrees caudally. Some practitioners take steps to examine the sacrum with AP projections in a perpendicular beam direction. Around the sacrum are reproductive organs that are sensitive to radiation, so it is necessary to select the right projection to reduce the radiation dose and show clear anatomical information. This study aims to determine the projection of an examination that produces clear anatomical information at a minimal dose. This is an experimental study with one shot post-test only. Samples in the form of radiographs were obtained from perpendicular AP and axial AP projections assessed by radiologists regarding the clarity of anatomical information. The radiation dose was measured using TLD on the ovaries and gonads. Data were analyzed by t-test and Wilcoxon test with an error level of 5%. The AP axial projection shows better anatomical information than the perpendicular AP projection. The axial AP projection shows a smaller dose of the ovaries and gonads. There is a difference in anatomical information between AP and axial AP projections with a p-value = 0.017. There was a difference in radiation dose between AP and axial AP projections on the right ovary (p-value = 0.002), left ovary (p-value less than 0.001) and gonads (p-value = 0.008).